2012
DOI: 10.4103/0975-7406.100244
|View full text |Cite
|
Sign up to set email alerts
|

Host modulation by therapeutic agents

Abstract: Periodontal disease susceptible group present advanced periodontal breakdown even though they achieve a high standard of oral hygiene. Various destructive enzymes and inflammatory mediators are involved in destruction. These are elevated in case of periodontal destruction. Host modulation aims at bringing these enzymes and mediators to normal level. Doxycycline, nonsteroidal anti-inflammatory drugs (NSAIDs), bisphosphonates, nitrous oxide (NO) synthase inhibitors, recombinant human interleukin-11 (rhIL-11), om… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 12 publications
(13 reference statements)
0
7
0
Order By: Relevance
“…Gingival inflammation that accompanies periodontal disease can damage supporting connective tissues and disrupt tooth anchoring to the jawbone. Several modulating agents have been investigated as potential therapies for periodontal disease, including antiproteinases, anti-inflammatory drugs, and bone-sparing drugs [1] .…”
Section: Introductionmentioning
confidence: 99%
“…Gingival inflammation that accompanies periodontal disease can damage supporting connective tissues and disrupt tooth anchoring to the jawbone. Several modulating agents have been investigated as potential therapies for periodontal disease, including antiproteinases, anti-inflammatory drugs, and bone-sparing drugs [1] .…”
Section: Introductionmentioning
confidence: 99%
“…Bacteria are essential for the development of periodontitis but not sufficient to cause disease alone. For periodontitis to develop, a susceptible host is required [ 28 , 29 ]. Page et al in 1999 reported that periodontal disease was characterized by high concentrations of matrix metalloproteinases (MMPs), cytokines, and prostaglandins in the periodontal tissue.23 Certain cytokines, including IL-1β and TNF-α, play a critical role in the pathogenesis of periodontitis.…”
Section: Discussionmentioning
confidence: 99%
“…Bacteria is an essential key to periodontitis, but it is not sufficient to cause the disease alone. Inflammatory mediators have been recorded to play a key role in periodontal tissue damage, as it is a double-edged sword [ 12 ]. Host modulation therapy is a treatment concept that aims to modify the host’s response towards the inflammatory process of a disease, reducing its damage ( Fig.…”
Section: Host Modulation Therapymentioning
confidence: 99%
“…Host modulation therapy (HMT), a term developed almost three decades ago, is an adjunct treatment strategy that aims to promote periodontal regeneration and restore the balance of pro-inflammatory mediators, as seen in healthy individuals [ 12 ]. While the use of sub antimicrobial-dose doxycycline (SDD) has been approved as an adjunct to conventional periodontitis treatment, studies have shown that non steroid anti-inflammatory drugs (NSAIDs) and bisphosphonate as HMT have raised some concerns.…”
Section: Introductionmentioning
confidence: 99%